Mitigating Ammonia Emissions and Enhancing Litter Quality in Commercial Broiler Chickens using Chemically Treated Litter during the Winter Season - V Patel, Jigar; M Trivedi, Manoj; J Modi, Rakesh; M Rajpura, Rais; P Madhavatar, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The experiment was conducted to mitigate ammonia emissions and enhance litter quality in commercial broiler chickens using chemically treated litter during the winter season (December-January, 2020-2021) in Anand, Gujarat. A total of 144 straight-run, day-old commercial broiler chicks were randomly distributed into six treatment groups. Each treatment group consisted of four replicates, each with six chicks, leading to 24 chicks per treatment. The six treatments used were: T1 - rice husk litter material (control group); T2 – husk treated with alum @ 90 g/sq.ft.; T3 - husk treated with boric acid (H3BO3) @ 24 g/sq.ft.; T4 - husk treated with sodium bisulfate (NaHSO4) @ 25 g/ sq.ft.; T5 - husk treated with a commercially available probiotic product @ 1 g/sq.ft.; T6 - husk treated with a commercially available Yucca schidigera liquid solution @ 1.0 mL/sq.ft. The litter treatment (T2 to T6) was applied on the 1st, 15th, and 29th days of the experiment. The study evaluated litter pH, moisture (%), nitrogen, and ammonia emissions (ppm) at the 6th week of age across different treatments in experiments. Results showed significantly lower pH, moisture, and ammonia emissions in T2, with the lowest ammonia levels observed in T2 (P<0.01). Litter nitrogen was significantly higher in T2 compared to other treatments (p<0.05). Based on the overall results of the experiment, it can be concluded that broiler birds reared on rice husk litter treated with alum (@ 90 g/sq.ft) exhibited reduced ammonia emissions and improved litter quality.